EXAMINING THE FACTORS INFLUENCING REPURCHASE INTENTION IN USING LION AIR - Rendika Nugraha; Annisa Ramadhanti (FIRM Journal of Management Studies, 2021)
The purpose of this study is to determine whether service quality, brand image, brand trust, and flight experience have influence towards repurchase intention in using Lion Air. This study is using quantitative method with 7 Likert-scale, from strongly disagree to strongly agree. The statements are adopted from various prior research. The data was distributed by online and directly to the person. The total sample used in this study is 347 respondents who ever flied with Lion Air at least twice from January 2019 to October 2019. The data was tested by using statistical software for validity and reliability and using Structural Equation Model for model fit and hypothesis testing. The findings indicate the factors that influencing customers repurchase intention in using Lion Air. Out of 6 hypotheses there are 4 hypotheses that are has a significant relationship which are service quality towards brand image, service quality towards brand trust, brand image towards brand trust, and brand trust towards repurchase intention. Meanwhile, the rest 2 hypotheses are found to be not significant, which are flight experience towards brand trust and brand image towards repurchase intention. There are many factors why it is rejected, such as price, needs, influence from others, the choice of routes, and frequent flight frequencies. This study is the first study that combine flight experience factor in determining customer repurchase intention in using Lion Air.